Investigating electrochemical deposition of gold on commercial off-the-shelf 3-D printing materials towards developing sensing applications. Issue 51 (22nd November 2022) - Partanen, Kristin; Pei, Yu; Hillen, Phillip; Hassan, Malek; McEleney, Kevin; Schatte, Gabriele; Payne, Sarah Jane; Oleschuk, Richard; She, Zhe
Abstract : Customized electrodes were made with 3-D printing and gold electrochemical reduction towards analytical applications. Abstract : The COVID-19 pandemic highlighted the inaccessibility of quick and affordable clinical diagnostics. This led to increased interest in creating low-cost portable electrochemical (EC) devices for environmental monitoring and clinical diagnostics. One important perspective is to develop new fabrication methods for functional and low-cost electrode chips. Techniques, such as electron beam and photolithography, allow precise and high-resolution electrode fabrication; however, they are costly and can be time-consuming. More recently, fused deposition modeling three-dimensional (3-D) printing is being used as an alternative fabrication technique due to the low-cost of the printer and rapid prototyping capability. In this study, we explore enhancing the conductivity of 3-D printed working electrodes with EC gold deposition. Two commercial conductive filament brands were used and investigated to fabricate electrode chips. Furthermore, strategies to apply epoxy glue and conductive silver paint were investigated to control the electrode surface area and ensure good electrical connection. This device enables detection at drinking water concentration thresholds. The practical application of the fabricated electrodes is demonstrated by detecting Cu 2+ using anodic stripping voltammetry.